The Problem of Healthkeeping of Children and Youth in Polish Educational Thought at the XV- beginning of XX century - Slyvka, Larysa (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The article presents the results of educational research actions in preserving and promoting the health of children and youth in the Polish educational theory and practice. The author analyzes the progressive ideas in the field of health oriented educational technologies which dominated in Polish educational thought during XV ‒ beginning of XX centuries. Rethinking of creative heritage of Polish scientists, educators and civic and educational leaders, opens up the new approaches and opportunities in implementing pedagogical aspects of healthkeeping of growing personality in Ukraine